The Effect of Treatment Ant Nest (Myrmecodia pendans) on Quail Production and Performance (Coturnix-coturnix japonica) - Gaol, Susan Elfitri Lumban; Sudjarwo, Edhy; Djunaidi, Irfan Hadji (The Journal of Experimental Life Science, 2016)
This research was aimed to determine the effect of ant nest treatment (Myrmecodia pendans) on quail production and performance. Research sample was 250 quails. Ant nest was administered in 5 treatments and 5 replications: P0 (0%) as control treatment, P1 (0.2%), P2 (0.4%), P3 (0.6%), and P4 (0.8 %) treatments. Data were collected from quails at 28 days to 70 days old. Variables measured were the performance and quail's egg production. This study was designed using completely randomized design. Real significant difference was examined utilizing Duncan's Multiple Range Test (DMRT). Analysis of variance result showed that ant nest provides significant influence to feed intake and Hen Day Production (P <0.05). The highest average of feed consumption is treatment P4 (0.8%), whereas treatment P0 (0%) was the lowest average for feed consumption. Feed conversion rate in treatment P4 (0.8%) was more efficient compared to other treatments. Ant nests administering did not result significantly different (P> 0.05) to feed conversion and egg mass. The results of the study concluded that higher ant nest administration is capable of increasing quails feed intake and Hen Day Production. Keywords: basal feed, flavonoids, productivity.